2015
DOI: 10.1007/s11010-015-2368-4
|View full text |Cite
|
Sign up to set email alerts
|

High salt diet modulates vascular response in A2AAR+/+ and A2AAR−/− mice: role of sEH, PPARγ, and KATP channels

Abstract: This study aims to investigate the signaling mechanism involved in HS-induced modulation of adenosine-mediated vascular tone in the presence or absence of adenosine A2A receptor (A2AAR). We hypothesized that HS-induced enhanced vascular relaxation through A2AAR and epoxyeicosatrienoic acid (EETs) is dependent on peroxisome proliferator-activated receptor gamma (PPARγ) and ATP-sensitive potassium channels (KATP channels) in A2AAR+/+ mice, while HS-induced vascular contraction to adenosine is dependent on solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(57 citation statements)
references
References 48 publications
5
52
0
Order By: Relevance
“…Additionally, sEH inhibition reduced A 1 AR-dependent aortic contractions in A 2A AR −/− mice [21]. These findings strongly suggested a potential role for sEH in regulating A 1 AR-dependent vascular function.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, sEH inhibition reduced A 1 AR-dependent aortic contractions in A 2A AR −/− mice [21]. These findings strongly suggested a potential role for sEH in regulating A 1 AR-dependent vascular function.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies revealed that a decrease in A 1 AR levels closely followed a decrease in sEH expression, and vice versa in sEH −/− and A 2A AR −/− mouse aortas [19, 21]. Additionally, sEH inhibition reduced A 1 AR-dependent aortic contractions in A 2A AR −/− mice [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations